Interior Design of Administrative Buildings and Their Role in Achieving the Effective Performance of the User - Aisha Samir Safwat; Hisham Zamil Hamdan (Journal of Techniques)
Formality pattern، which gave a sense of formal equilibrium without any obstruction or confusion، resulting from a combination،Conclusions، inter alia، that the functional performance of administrative spaces is reflected in a comfortable internal environment. Using environmental control systems (air conditioning، sound control and fire detection systems)، they play an effective role In changing the inner atmosphere of spaces، it is also a key factor for psychological well-being،Reassurance (safety and security)، which in turn is reflected in the nature of the functionality of users within the internal space.